Molecular Recognition of Natural and Non‐Natural Substrates by Cellodextrin Phosphorylase from Ruminiclostridium Thermocellum Investigated by NMR Spectroscopy. Issue 63 (8th October 2021) - Gabrielli, Valeria; Muñoz‐García, Juan C.; Pergolizzi, Giulia; de Andrade, Peterson; Khimyak, Yaroslav Z.; Field, Robert A.; Angulo, Jesús
Abstract: β‐1→4‐Glucan polysaccharides like cellulose, derivatives and analogues, are attracting attention due to their unique physicochemical properties, as ideal candidates for many different applications in biotechnology. Access to these polysaccharides with a high level of purity at scale is still challenging, and eco‐friendly alternatives by using enzymes in vitro are highly desirable. One prominent candidate enzyme is cellodextrin phosphorylase (CDP) from Ruminiclostridium thermocellum, which is able to yield cellulose oligomers from short cellodextrins and α‐d ‐glucose 1‐phosphate (Glc‐1‐P) as substrates. Remarkably, its broad specificity towards donors and acceptors allows the generation of highly diverse cellulose‐based structures to produce novel materials. However, to fully exploit this CDP broad specificity, a detailed understanding of the molecular recognition of substrates by this enzyme in solution is needed. Herein, we provide a detailed investigation of the molecular recognition of ligands by CDP in solution by saturation transfer difference (STD) NMR spectroscopy, tr‐NOESY and protein‐ligand docking. Our results, discussed in the context of previous reaction kinetics data in the literature, allow a better understanding of the structural basis of the broad binding specificity of this biotechnologically relevant enzyme. Abstract : Understanding the molecular basis of the broad specificity of cellodextrin phosphorylase (CDP) from Ruminiclostridium thermocellum, can facilitate the generation of highly diverse CDP‐catalysed cellulose‐based structures. Here, NMR spectroscopy and molecular modelling allowed to understand how CDP is able to bind non‐natural chemically modified donors and acceptors with different binding epitopes, revealing the structural requirements for CDP ligands, which will enable exploitation of CDP to produce novel materials of high biotechnological interest.